A Study on the Decomposition of SPS and Its Effects on Via Filling Performance. (7th April 2015) - Kimizuka, Ryoichi; Toda, Hisayuki; Eda, Tetsuro; Kishimoto, Kazuki; Takaya, Yasuko; Oh, Reisei; Takai, Osamu
Abstract : Electrolytic copper via filling based on three additive component copper sulfate bath chemistry has been and currently is widely used in electronic packaging. Progression in copper sulfate plating chemistry is vital to development of smart phones among other devices. In order to further elucidate bath chemistry and possible methods to improve performance, degradation of the disodium 3, 3'-dithiobis(1-propanesulfonate) (SPS) additive, which is employed as brightener, during copper via filling by electrodeposition and the influence of a byproduct on plating was investigated. Oxidative decomposition of SPS and formation of disodium 1, 3-propanedisulfonate (PDS) at an IrO2 coated Ti insoluble anode during electrolysis was confirmed by NMR analysis. By addition to a fresh bath, PDS was then shown to compromise via filling performance. This study clarified the anodic oxidation of SPS to PDS under electrolytic filling conditions and that the PDS concentration correlated to the filling ability of the copper plating bath.